Showing up when it counts : 2021 Annual report - Youth Employment Services (YES) (2022)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2022)

Entrepreneurs and Artists in the Time of COVID-19 - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, Canadian governmental agencies and other organizations have deployed multiple programs to support local entrepreneurs and their businesses. In the current evolving situation, it’s hard to know where to turn. This document contains some of the currently available programs and resources for entrepreneurs and will be updated periodically. Last updated on July 27, 2020.

YES Program Book - Youth Employment Services (YES) (2020)
issued: September, 2020/December, 2020

Small Business Resource Guide - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, we have compiled a resource guide for small businesses to help you navigate these challenging times.

Program Book - Youth Employment Services (YES) (2020)
issued: January, 2020/December, 2020

Employment in the Québec Regions : Needs Assessment Study - Youth Employment Services (YES) (2017)
The current needs assessment was developed with the vision of understanding the socioeconomic conditions of seven Quebec regions examined by this study, namely, Gaspésie-Îles-de-la-Madeleine, Capitale-Nationale, Chaudière-Appalaches, Estrie, Montérégie, Côte-Nord and Abitibi-Témiscamingue. The study also involved conducting an inventory of job search and employment-related services in these seven Québec regions, and identifying the needs of English-speaking job seekers residing in the regions. The intent of this study is to inform the development of timely, evidence-based English-language employment services and career supports in the regions, ultimately leading to increased economic opportunities and stability for English-speaking youth (aged 16-35) in Québec. A related goal is to increase awareness of English-language employment services and supports available to job seekers in the Québec regions.

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Quebec Employment Service Providers Conference (2008)

Congrès des Fournisseurs de Sercices d'emploi du Québec (2008)

Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Program Book for Winter/Spring 2017 - Youth Employment Services (YES) (2017)
issued: January, 2017/August, 2017

Program Book for Winter/Spring 2016 - Youth Employment Services (YES) (2016)
issued: January, 2016/August, 2016

Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)
issued: January, 2018/August, 2018

Program Book - Youth Employment Services (YES) (2013)
issued: Winter, 2013/Spring, 2013

The YES Holiday Job Rush Campaign : Getting Montreal's Youth into the Workforce - Youth Employment Services (YES) (2009)

Incorporating a Business - Youth Employment Services (YES)

Business Expenses - Youth Employment Services (YES)

Government Filing Requirements - Youth Employment Services (YES)

Market Research Essentials - Youth Employment Services (YES)

Website and E-Commerce Fundamentals - Youth Employment Services (YES)

Best Social Media Practices - Youth Employment Services (YES)

Best Hiring Practices - Youth Employment Services (YES)

Employee Contract & Handbook - Youth Employment Services (YES)

Setting Up an Employee File - Youth Employment Services (YES)

Helping Montreal's Youth into the Workforce - Youth Employment Services (YES) (2011)

Regional Resources for Employment - Youth Employment Services (YES)

Presentation by Youth Employment Services (YES) to the Standing Senate Committee on Official Languages and the English-speaking Community in Quebec - Youth Employment Services (YES) (2017)
YES (Youth Employment Services) is a non-for-profit charity whose mission is to enrich the community by providing English-language services to help people find jobs and start small and medium size businesses.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2018-2019 / Rapport annuel 2018-2019 - Youth Employment Services (YES) (2019)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2019-2020 : Broadening Access for Better Futures - Youth Employment Services (YES) (2020)

Recommendations from the Youth Unemployment Forum Held on December 5, 2017 - Youth Employment Services (YES) (2018)
In Quebec and indeed across Canada we are confronting the many and varied challenges of a rapidly evolving labour market. New technologies are developing at a rate that is challenging our institutions; globalization is bringing increasing unpredictability to economic systems; traditional management models are being disrupted by the growing sharing and gig economies. Youth may have adapted quickly to high-tech society, however it would be disastrous to assume they will adjust as easily to the trials of the Fourth Industrial Revolution. Today’s youth need innovative supports to help them to survive in and capitalize on the complexities of the future economy. While Québec youth have never been more highly educated or bilingual, young job seekers andemployers alike are frustrated. Not enough has been done to curb the outmigration of educated youth nor to create an equitable environment for underrepresented populations. It hardly matters that jobs may be available, if youth are not here or not able to connect with them. This is why, with support from Canadian Heritage, on December 5th, 2017 YES convened a daylong forum bringing together multiple sectors from throughout the province of Quebec, to develop a deeper understanding of the unique employment barriers faced by Quebec’s Official Language Minority Community (OLMC) youth.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2020-2021 - Youth Employment Services (YES) (2021)
As a not-for-profit organization, YES enriches the community by providing English-language support services to help Quebecers find employment and start and grow businesses. YES Employment + Entrepreneurship has been broadening access to opportunities for Quebec’s English-speaking community for over 25 years now. As we reflect on the organization’s 25th anniversary in the midst of the pandemic, we are reminded of the vital importance of our career and business support services.

Who We Are - Youth Employment Services (YES) (2020)

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

New Online Service Makes Expert Advice Accessible and Affordable - Youth Employment Services (YES) (2011)

YES Montreal Kicks Off its Summer Job Campaign : Close to 1000 Available Positions - Youth Employment Services (YES) (2010)

Young Quebec Artists Encouraged to Turn their Passion into Profit - Youth Employment Services (YES) (2011)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

With the Help of YES, the Creative Workforce Turns Passion into Profit : Premières To Showcase Emerging Artists - Youth Employment Services (YES) (2010)

YES Montreal Helps Entreprenuers Capitalize on Opportunities at the 13th Annual Entrepreneurship Conference : Made in Montreal - Youth Employment Services (YES) (2010)

YES E-News : April 2009 - Youth Employment Services (YES) (2009)
Number of pages: 1

YES E-News Monthly - Youth Employment Services (YES)
Number of pages: 1

YES E-News : September 2007 - Youth Employment Services (YES) (2007)
Number of pages: 1

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)
Number of pages: 4

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)
Number of pages: 2

Making your Job Search Work for You - Youth Employment Services (YES)

Fall 2016: Program Book : September 2016 - December 2016 - Youth Employment Services (YES) (2016)

Fall 2017 : Program Book : September 2017 - December 2017 - Youth Employment Services (YES) (2017)

Fall Program Book : September - December 2021 - Youth Employment Services (YES) (2021)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)

Winter/Spring 2013 Program Book - Youth Employment Services (YES) (2013)

Winter/Spring 2008 Program Book - Youth Employment Services (YES) (2008)

Winter/Spring 2009 Program Book - Youth Employment Services (YES) (2009)

Program Book: Winter / Spring 2007 - Youth Employment Services (YES) (2007)

Winter/Spring 2014 Program Book - Youth Employment Services (YES) (2014)

Fall 2008 Program Book - Youth Employment Services (YES) (2008)

Getting Motivated & Staying Focused - Youth Employment Services (YES) (2009)

YES Montreal Presents the Meet the Experts Seminar Series : Focus on the Growing Trends in Green Businesses and Social Entrepreneurship - Youth Employment Services (YES) (2007)

The 11th YES Entrepreneurship Conference : March 8/2008 - Youth Employment Services (YES) (2008)

The 10th Anniversary YES Entrepreneurship Conference : March 3/2007 - Youth Employment Services (YES) (2007)

9th Quebec Employment Service Providers Conference : The Greatest Challenges and Best Practices of Employment Service Professionals - Youth Employment Services (YES) (2011)

The 10th Annual YES Entrepreneurship Conference : YES, The Future is Yours : Workshops - Youth Employment Services (YES)

Jump Start Your Job Search : Readiness Questionnaire - Youth Employment Services (YES)

The 19th Annual Entrepreneurship Conference - Youth Employment Services (YES)

6th Montreal Self-Employed Artists Conference - Youth Employment Services (YES) (2006)

YES' Artists' Conference: Business Skills for Creative Souls - Youth Employment Services (YES) (2013)

Entrepreneurship & Artists' Online Program : Winter/Spring 2012 - Youth Employment Services (YES) (2012)

Closing the 12k Gap : Improving Employment for Quebec's English Community - Conference Report - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Youth Employment Services (YES) is pleased to have secured funding from the Secretariat for relations with English-peaking Quebecers (SRQEA) to build a stronger network of English service organizationsworking in employability. The Provincial Employment Roundtable (PERT) project aims to address three important employment issues facing English speakers in Quebec.

Combler l'écart de 12 000 Emplois : améliorer l'emploi pour la communauté d'expression anglaise du Québec - rapport de conférence - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Services d’emploi pour les jeunes (YES) est heureux d’avoir obtenu du ﬁnancement du Secrétariat des relations avec les Québécois anglophones (SRQEA) aﬁn de bâtir un réseau plus solide d’organismes de services en anglais qui travaillent dans le domaine de l’emploi. Le projet de la Table ronde provinciale sur l’emploi (PERT) a pour objectif d’aborder trois questions importantes en matière d’emploi auxquelles doivent faire face les anglophones au Québec.

Transferable Skills & Your 2020 Job Search - Voice of English-speaking Quebec (VEQ); Youth Employment Services (YES) (2020)

Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)